2008
DOI: 10.1016/j.jvs.2008.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Colonic ischemia complicating open vs endovascular abdominal aortic aneurysm repair

Abstract: CI is significantly more common after open AAA repair and is associated with increased morbidity and a two- to fourfold increase in mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 34 publications
3
61
0
3
Order By: Relevance
“…Female gender was associated with increased incidence of IC in two studies [9,10] . The natural logarithm of a disease severity score was recognised as positively associated with development of ischaemic colitis (mean severity score in IC 1311 vs 389 in no-IC, p<0.001) [9] . This disease severity score is a proprietary measure developed by Medstat (Ann Arbor, Michigan, USA) and is based on hospital admissions and discharges in the USA.…”
Section: Patient Factorsmentioning
confidence: 94%
See 2 more Smart Citations
“…Female gender was associated with increased incidence of IC in two studies [9,10] . The natural logarithm of a disease severity score was recognised as positively associated with development of ischaemic colitis (mean severity score in IC 1311 vs 389 in no-IC, p<0.001) [9] . This disease severity score is a proprietary measure developed by Medstat (Ann Arbor, Michigan, USA) and is based on hospital admissions and discharges in the USA.…”
Section: Patient Factorsmentioning
confidence: 94%
“…The reported rates of ischaemic colitis after elective surgery ranged from 0% to 4.6% [11,12] versus 5% to 20.5% [13,14] after emergency surgery. Six studies looked in more depth at emergency presentations and found those who had ruptured aneurysm demonstrated a higher rate of IC compared to those who had not ruptured (3.2 to 6.4 times more likely in ruptures) [9,13,15,10,16,17] . The studies reporting this are retrospective cohort studies.…”
Section: Pre-operative Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…ABES = angioplasty and balloon-expandable stent placement; CA = celiac artery; COPD = chronic obstructive pulmonary disease; IMA = inferior mesenteric artery; LSCI = left-side colon ischemia; RSCI = right-side colon ischemia; SMA = superior mesenteric artery. 2 A pathogenic role of large artery hypoperfusion is manifested when colon ischemia occurs after the IMA is sacrificed during surgery for abdominal aortic aneurysm 19,20 or colon resection, 21 as in case 4 (Table 2), eliminating a critical source of collateral supply to the distribution of a diseased SMA. Therapy of visceral artery occlusion is effective.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…The most common abdominal aneurysm occurs in the aorta, hence the term abdominal aortic aneurysm (AAA). Ischemic colitis is the most common complication after abdominal aortic aneurysm surgery (38,39) presenting a high impact in mortality rates (40)(41)(42)(43). Another high risk postoperative complication is the leakage of a low rectal anastomosis connection, or the site where the two transacted bowel segments are joined again, closing the bowel lumen (44).…”
Section: Intestinal Ischemia and Its Role In Septic Shockmentioning
confidence: 99%